Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO